When ALL the forces are equal, or in general when <span>forces in the opposite direction are equal
so we can have newton example:
10 newtons X -10 newtons
netforce = 0 newtons</span>
Answer:
1.6 m/s2
Explanation:
Let
be the gravitational acceleration of the moon. We know that due to the law of energy conservation, kinetic energy (and speed) of the rock when being thrown upwards from the surface and when it returns to the surface is the same. Given that
stays constant, we can conclude that the time it takes to reach its highest point, aka 0 velocity, is the same as the time it takes to fall down from that point to the surface, which is half of the total time, or 4 / 2 = 2 seconds.
So essentially it takes 2s to decelerate from 3.2 m/s to 0. We can use this information to calculate ![g_m](https://tex.z-dn.net/?f=g_m)
![g_m = \frac{\Delta v}{\Delta t} = \frac{0 - 3.2}{2} = \frac{-3.2}{2} = -1.6 m/s^2](https://tex.z-dn.net/?f=g_m%20%3D%20%5Cfrac%7B%5CDelta%20v%7D%7B%5CDelta%20t%7D%20%3D%20%5Cfrac%7B0%20-%203.2%7D%7B2%7D%20%3D%20%5Cfrac%7B-3.2%7D%7B2%7D%20%3D%20-1.6%20m%2Fs%5E2)
So the gravitational acceleration on the Moon is 1.6 m/s2
Explanation:
Given that,
Mass of the hamster, m = 0.139 kg
Diameter of the wheel, d = 20.8 cm
Radius, r = 10.4 m
Frequency of the wheel, f = 1 Hz
Time, t = 0.823 s
(a) There exist a relationship between the tangential and angular acceleration of the wheel. It is given by :
![a=\alpha \times r](https://tex.z-dn.net/?f=a%3D%5Calpha%20%5Ctimes%20r)
Since, ![\alpha =\dfrac{\omega}{t}](https://tex.z-dn.net/?f=%5Calpha%20%3D%5Cdfrac%7B%5Comega%7D%7Bt%7D)
![a=\dfrac{\omega}{t} \times r](https://tex.z-dn.net/?f=a%3D%5Cdfrac%7B%5Comega%7D%7Bt%7D%20%5Ctimes%20r)
![a=\dfrac{2\pi f}{t} \times r](https://tex.z-dn.net/?f=a%3D%5Cdfrac%7B2%5Cpi%20f%7D%7Bt%7D%20%5Ctimes%20r)
![a=\dfrac{2\pi \times 1}{ 0.823} \times 10.4\times 10^{-2}](https://tex.z-dn.net/?f=a%3D%5Cdfrac%7B2%5Cpi%20%5Ctimes%201%7D%7B%200.823%7D%20%5Ctimes%2010.4%5Ctimes%2010%5E%7B-2%7D)
![a=0.793\ m/s^2](https://tex.z-dn.net/?f=a%3D0.793%5C%20m%2Fs%5E2)
(b) In radial direction, applying the second law of motion as :
![N-mg=ma](https://tex.z-dn.net/?f=N-mg%3Dma)
a is the radial acceleration, ![a=\dfrac{v^2}{r}](https://tex.z-dn.net/?f=a%3D%5Cdfrac%7Bv%5E2%7D%7Br%7D)
![N=mg+ma](https://tex.z-dn.net/?f=N%3Dmg%2Bma)
![N=mg+m(\dfrac{v^2}{r})](https://tex.z-dn.net/?f=N%3Dmg%2Bm%28%5Cdfrac%7Bv%5E2%7D%7Br%7D%29)
![N=mg+m(\dfrac{(r\omega)^2}{r})](https://tex.z-dn.net/?f=N%3Dmg%2Bm%28%5Cdfrac%7B%28r%5Comega%29%5E2%7D%7Br%7D%29)
![N=mg+m\omega^2 r](https://tex.z-dn.net/?f=N%3Dmg%2Bm%5Comega%5E2%20r)
![N=m(g+\omega^2 r)](https://tex.z-dn.net/?f=N%3Dm%28g%2B%5Comega%5E2%20r%29)
![N=m(g+(2\pi f)^2 r)](https://tex.z-dn.net/?f=N%3Dm%28g%2B%282%5Cpi%20f%29%5E2%20r%29)
![N=0.139\times (9.8+(2\pi 1)^2\times 10.4\times 10^{-2})](https://tex.z-dn.net/?f=N%3D0.139%5Ctimes%20%289.8%2B%282%5Cpi%201%29%5E2%5Ctimes%2010.4%5Ctimes%2010%5E%7B-2%7D%29)
![N=1.93\ N](https://tex.z-dn.net/?f=N%3D1.93%5C%20N)
Hence, this is the required solution.
Answer:
Endothermic reaction
Explanation:
If the reaction releases less energy than the energy needed to start the chemical reaction, then the reaction takes energy from the system. An endothermic reaction is a reaction that will takes energy from the system. Those energies will be put into the product of the reaction, make the product have higher potential energy than the reactant. The product of this reactant will be less stable since it's at a high energy state.